A Study of ICT Facility Readiness and Teachers’ Use of ICT Facilities in The Escola Técnica Professional Becora Dili and The Técnica Professional Dom Bosco Fatumaca Baucau, Dili Timor-Leste - de Almeida Belo, Feliciano; Ye, Yan (Scholar: Human Sciences, 2016)
This study examines the availability and usability of Information and communication technology among the two technical high school teachers in the Escola Técnica Profissional Becora, Dili and the Escola Técnica Profissional Dom Bosco Fatumaca Baucau, Dili, Timor-Leste. The Research Design employed is the quantitative, descriptive and comparative survey design. Four research questions were formulated for the study. The population for the study consisted of 90 technical high school teachers. Questionnaire was used as the instrument for gathering data for the study. Data collected were analyzed using means standard deviation and independent samples t-test (two-tailed). Results of the study showed that ICT facilities are not available in most of the schools covered. It was also observed most teachers used as the sample for the study, are not competent in the use of ICT. Recommendations were then made to the administrators, principals the two schools, and teachers, schools in Timor-Leste, MOE Timor-Leste and future researchers.